(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Fetal movement counting is a way to check the health of a woman’s unborn baby (fetus). It’s often called kick counting. It’s done by counting the number of kicks you feel from your baby in the uterus in a certain time period. The objective of the study were to assess the maternal compliance among experimental group 1 of antenatal mother after Cardiff count 10 chart on assessment of fetal movement, assess the maternal compliance among experimental group 2 of antenatal mother after DFMC chart on assessment of fetal movement, determine the effectiveness maternal compliance of Cardiff count 10 chart versus DFMC chart on assessment of fetal movement among antenatal mother and find out the association on between posts tests score on maternal compliance experiment group I and II with selected hospital Kanpur. A experimental multi factorial design was used for this study, simple random sampling techniques was used and Sample size was 60. The result of the study showed that the overall mean score during Cardiff count ten chart (65.83) and overall mean score during DFMC chart (50.90).Highly significant difference was found between DFMC chart and Cardiff count ten chart fetal movement score. Highly significant between fetal movement score of antenatal mother in Cardiff count ten chart versus DFMC chart and their age, education, occupation , type of family, food habit, source of information, the obtained value was more the table value . So it was proven that there was association between variables with the overall Cardiff count ten chart versus DFMC chart assessment of fetal movement.